Low-dose dobutamine infusion and single-dose tocilizumab in acute myocardial infarction patients with high risk of cardiogenic shock development - rationale and design of the DOBERMANN trial. (3rd May 2023) - Bo Kunkel, J; Frydland, M; Duus Holle, S; Kjaergaard, J; Pecini, R; Evi Bang, L; Palm, P; Wiberg, S; Holmvang, L; Engstroem, T; Loenborg, J; Eifer Moeller, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Novo Nordisk Fonden Background: Cardiogenic shock (CS) is seen in up to 10% of patients with ST-elevation myocardial infarction (STEMI) and is associated with a high mortality rate of up to 50%. Approximately 1/3 of STEMI-patients developing CS are not in overt shock at time of hospital admission but will develop hemodynamical instability within the following hours to days. Patients at risk of CS development may be clinically stable but with normal lactate levels (Society for Cardiovascular Angiography and Interventions classification, SCAI A/B). The Observatoire Régional Breton sur l'Infarctus (ORBI) clinical risk score has recently been developed and validated for predicting the risk of in-hospital (late) CS. STEMI-patients with an ORBI score >=10 have a risk of in-hospital CS development of more than 8-10%. NTproBNP is a biomarker released from the myocardium reflecting neurohormonal activation which is strongly correlated with hemodynamic parameters. Neurohormonal activation as well as a systemic inflammatory response are present acutely at hospital admission in STEMI patients developing late CS compared to non-CS patients suggesting an early subclinical hemodynamic deterioration. Dobutamine induces significant positive inotropic- and dose-dependent chronotropic effects and decreases afterload by peripheral vasodilatation, which increases cardiac output and organ perfusion. The interleukin-6 receptor antagonist Tocilizumab has been shown to reduce troponin leakage and increase myocardial salvage in acute MI patients. The effects of Dobutamine and Tocilizumab in a high-risk population have not previously been investigated. Methods: DOBERMANN is an investigator-initiated, double blinded randomized clinical trial. Consecutive patients with acute MI admitted for acute coronary angiography and treated with percutaneous coronary intervention are screened with the ORBI risk score in the catheterization laboratory. One hundred adult patients presenting without CS at hospital admission with an intermediate-high risk of CS development (ORBI risk score of >=10) will be randomized 2x2 to receive a continuous intravenous infusion of dobutamine (5 micrograms/kg/minute, 24h) vs. placebo, and a single dose of Tocilizumab (280 mg, 1h) vs. placebo. NTproBNP as a proxy for development of CS and hemodynamic instability will be sampled for primary endpoint analysis. Effects on clinical parameters, mortality, morbidity as well as specific indicators of inflammation, cardiac function, and infarct size will secondarily be assessed noninvasively at 48h and at three months follow-up. Enrollment began in March 2022 and is commencing as planned. Discussion: We hypothesize that inflammatory and neurohormonal responses are associated with subclinical hemodynamic instability in patients with AMI with intermediate/high risk of CS. The potentially unstable condition may be targeted pharmacologically as an add-on to existing therapy. Design Overview Sampling Timeline